Modelagem espacial aplicada na seleção de áreas favoráveis para implantação de um aterro sanitário no município de Bujaru-PA - REIS, Antônio Nonato Correa dos (2020)
One of the major problems facing today's society is the production of tailings that are byproducts of Urban Solid Waste - MSW, which somehow cannot or cannot be reused. It is in this context that spatial modeling techniques were applied as a case study to select favorable areas for the installation of a landfill in the city of Bujaru - PA. To this end, geospatial data were raised in order to create a geographic database, as well as the definition of a methodology based on multicriteria analysis, weighted factor overlapping technique and bibliographic survey related to the theme. Given this, it was found that there are about 1,895 favorable hectares for the construction of a dump in Bujaru, before this were selected 3 areas considered the best to validate the elaborated methodology. The application of spatial modeling using geoprocessing techniques proved to be adequate to enable, through local reality, the determination of areas suitable for the landfill installation, thus avoiding costs and mitigating negative environmental impacts.